Computational Evidence Based Perspective on the Plausible Repositioning of Fluoroquinolones for COVID-19 Treatment - Yadav, Vikas (Current Computer - Aided Drug Design, 2022)
The coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has become a serious global healthcare crisis, so there is an emergence of identifying efficacious therapeutic options. In a setting where there is an unavailability of definitive medication along with the constant eruption of vaccine-related controversies, the drugrepositioning approach seems to be an ideal step for the management of COVID-19 patients. Fluoroquinolones (FQs) are commonly prescribed antibiotics for the treatment of genitourinary tract and upper respiratory tract infections, including severe community-acquired pneumonia. Research over the years has postulated multifaceted implications of FQs in various pathological conditions. Previously, it has been reported that few, but not all FQs, possess strong antiviral activity with an unknown mechanism of action. Herein, an interesting perspective is discussed on repositioning possibilities of FQs for the SARS-CoV-2 infections based on the recent in silico evidential support. Noteworthy, FQs possess immunomodulatory and bactericidal activity which could be valuable for patients dealing with COVID-19 related complications. Conclusively, the current perspective could pave the way to initiate pre-clinical testing of FQs against several strains of SARS-CoV-2.
Keywords: drug repositioning